Religious Experience and Heavenly Cult in the Ascension of Isaiah - Lech, Leszek Antoni (Trinity College Dublin. School of Religion, Theology, and Peace Studies, 2025)
This study aims to address a gap in Second Temple scholarship by examining how religious groups engage with the divine realm within this two-staged apocalypse, as conveyed by implied authors alongside implied readers and hearers. Indeed, the phenomenon of Isaiah’s ascent (i.e., AscIs 6:10–12) and his celestial journey (i.e., AscIs 7:2–11:35), respectively described and narrated in stage one, occurs during collective prophetic liturgy and raises questions about the religious experiences of prophetic groups related to the Ascension of Isaiah. The research presented here addresses the central message of the Ascension of Isaiah. This message is transmitted orally and, embedded within this book, which was written in two stages, became the central thread uniting this composite work and making it coherent. This composition is about Isaiah, who, surrounded by a group of devotees involved in a religious celebration, had a religious encounter. This central theme reflects the sensibility of its authors and, consequently, was found appealing to those who received it. As this study demonstrates, signs behind this message indicate a genuine religious experience of its authors and their precursors. The magnificence of Isaiah’s account goes beyond the marvellous story about the ascended and transformed human being meeting the divine. This research exhibits how the visionary account’s numinous narratives are a script for its performance which might have stimulated devotees to re-enact the experience of Isaiah. This study seeks to demonstrate just how central the motif of the human encounter with the divine, attained through the liturgical-prophetic rituals in “communitas”, was for the authors of the apocalypse, its readers and listeners. It also might nurture questions about how vital the experiences of heavenly journeys and feelings of “oneness” with the divine were for the early Christians.
APPROVED